2003
DOI: 10.1007/s00701-003-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Mild head injury ? mortality and complication rate: meta-analysis of findings in a systematic literature review

Abstract: Of 1000 patients arriving at hospital with mild head injury, 1 will die, 9 will require surgery or other intervention, and about 80 will show pathological findings on CT. At least these 8% of patients will probably need in-hospital care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 50 publications
0
47
0
3
Order By: Relevance
“…In a Swedish study from 1998 the proportion of patients with mild TBI who underwent a CT scan was reported to vary from a few percent to 80%-on average, 22% (Borg et al, 2000). Several studies have proposed that the early use of a CT scan after mild TBI instead of in-hospital observation saves costs (Stein et al, 1991;Ingebrigtsen and Romner, 1996;Borg et al, 2000;Af Geijerstam and Britton, 2003). However, even though most patients with mild TBI have normal CT findings, every clinician should be aware that there will always be a few patients who can develop hemorrhagic lesions (Borg et al, 2000).…”
Section: Epidemiology Of Brain Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Swedish study from 1998 the proportion of patients with mild TBI who underwent a CT scan was reported to vary from a few percent to 80%-on average, 22% (Borg et al, 2000). Several studies have proposed that the early use of a CT scan after mild TBI instead of in-hospital observation saves costs (Stein et al, 1991;Ingebrigtsen and Romner, 1996;Borg et al, 2000;Af Geijerstam and Britton, 2003). However, even though most patients with mild TBI have normal CT findings, every clinician should be aware that there will always be a few patients who can develop hemorrhagic lesions (Borg et al, 2000).…”
Section: Epidemiology Of Brain Injuriesmentioning
confidence: 99%
“…In a meta-analysis of epidemiological high-quality studies of mild TBI, Af Geijerstam and Britton (2003) concluded that about 8% of the patients will show pathological findings on CT and about 1% will require surgery. Thus, TBI classified as mild may have serious, sometimes life-threatening, complications.…”
Section: Epidemiology Of Brain Injuriesmentioning
confidence: 99%
“…Tačiau komplikacijos, kurios būdingos ūminei traumai, lengvos galvos smegenų traumos atveju yra santykinai retos -intrakranijinių pažei-dimų rizika apie 10% [15] (sumušimas, subdūrinė ar epidūrinė hematomos, smegenų patinimas, subarachnoidinė hemoragija). 1% nustatytų pakitimų reikalauja neurochirurginio gydymo [15][16][17][18], mirtingumas tarp suaugusiųjų 0,1 % ir dar mažesnis tarp vaikų [19][20].…”
Section: Sveikatos Mokslai / Health Sciences In Eastern Europeunclassified
“…[6][7][8][9][10][11][12] With the advent of routine head CT scanning of virtually all patients with head injury, it has become clear that a substantial number (6%-10%) of patients with minor head injury have evidence of neurocranial traumatic complications. [13][14][15][16][17][18] Functional outcome in these patients with so-called "complicated" minor head injury has been shown to be significantly poorer than that in patients without neurocranial traumatic complications after minor head injury. 19,20 Long-term outcome in terms of functional disability or postconcussive symptoms in patients with complicated minor head injury specifically, however, is still largely unknown.…”
mentioning
confidence: 99%